2019
DOI: 10.1111/aen.12433
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐derived medicinal entomochemicals: an integrated approach to biodiscovery in Australia

Abstract: Despite an ancient and well‐established use of insects in traditional medicine, our understanding of their bioactive compounds (entomochemicals) lags far behind that of medicinal plants (phytochemicals). In this review, we focus particularly on insect–plant interactions, to examine the possible dependence of the medicinal properties of insects on phytochemicals that they bioaccumulate or chemically modify. We suggest that a cross‐disciplinary approach including ethnobiology, insect ecology and phytochemistry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…It is remarkable that several species of Camponotus such as Camponotus maculatus and Camponotus pennsylvanicus have been employed as traditional remedy in Burkina Faso, West Africa and India (Mazurkiewicz et al, 2016;Schrader et al, 2016;Salyer, 2018;Buczkowski, 2019;Ouango et al, 2022;Siddiqui et al, 2023b), whereas, Camponotus inflatus is consumed by Aboriginal Australian in Australia as part of their diet for the source of natural sugar. They mix the ants with salads which is responsible for sweet sour flavour in their dish (Faast and Weinstein, 2020;Islam et al, 2022;Dong et al, 2023). In Neotropical countries (i.e.…”
Section: Records Of Consumption and Consumer Acceptance Of Edible Bla...mentioning
confidence: 99%
“…It is remarkable that several species of Camponotus such as Camponotus maculatus and Camponotus pennsylvanicus have been employed as traditional remedy in Burkina Faso, West Africa and India (Mazurkiewicz et al, 2016;Schrader et al, 2016;Salyer, 2018;Buczkowski, 2019;Ouango et al, 2022;Siddiqui et al, 2023b), whereas, Camponotus inflatus is consumed by Aboriginal Australian in Australia as part of their diet for the source of natural sugar. They mix the ants with salads which is responsible for sweet sour flavour in their dish (Faast and Weinstein, 2020;Islam et al, 2022;Dong et al, 2023). In Neotropical countries (i.e.…”
Section: Records Of Consumption and Consumer Acceptance Of Edible Bla...mentioning
confidence: 99%
“…For these groups, the honeypot ant represents their Dreaming or Tjukurpa , the Aboriginal philosophy based on the spiritual interrelation of people and things. In addition to their use as a food source, there are records of honeypot ant honey being used to treat sore throats and colds ( Faast & Weinstein, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds such as phenols, flavonoids, terpenes, saponins, sugars, alkaloids, glycosides and fatty acids, identified in a wide variety of insects, have demonstrated biological properties including antioxidant, anti-inflammatory, antiproliferative, cytotoxic, analgesic, immunomodulatory, antidiabetic, cardioprotective, antihypertensive, antimicrobial properties. Analysis of literature data demonstrated that a number of extracts, peptides, and synthetic analogues exhibite anti-inflammatory properties [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%